Acesso de crianças com condição crônica na atenção primária em saúde: percepções de profissionais - Rodrigues, Daisy Cristina (2017)
Children with chronic conditions are expressive in the health services, having as one of the reference services Primary Health Care. In this sense, the objective is to describe the child's access in chronic condition to primary health care from the perspective of health professionals And to identify the presence of the essential attributes of the primary care to the child with chronic condition in the perception of the health professionals. This is an exploratory and descriptive study, with a qualitative approach. To collect data, we conducted semi-structured interviews with twenty-eight health professionals who are part of the Basic Health Units and the Family Health Strategy teams of the municipality of Santa Maria - Rio Grande do Sul. Data collection took place in the months of April to August 2016, the recommendations were followed and the regulatory norms of research involving human beings were respected. The data were organized with the aid of QDA Miner 3.2 software, and treated through the thematic analysis of the inductive type. The analysis of the participants' statements emerged three units of meaning: "Knowing the chronic condition", which addressed the meaning of chronic condition in childhood for professionals, and also identified the main conditions that affect the children of these health services, predominating problems Respiratory. The suggestive unit of meaning refers to "Health professionals' experiences and perceptions about access" points to the meaning of access, as it occurs, and the aspects favor and limit the effectiveness of this attribute. The third unit of meaning "(Re) knowing the attributes of Primary Health Care" reveals weaknesses in the attributes Integrality of care to children with chronic condition, Longitudinality during health care and Coordination of care. It is believed that the study can contribute with subsidies for the planning of care for the child with chronic condition, making it possible to access and strengthen the attributes of the other attributes of Primary Health Care in child care.